2018
DOI: 10.2399/ana.18.020
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc heights and concavity index of the lumbar spine in young healthy adults

Abstract: Objectives: The aim of this study was to investigate lumbar intervertebral disc heights and concavity index of the lumbar spine, and the influence of age, gender, weight, height and body mass index (BMI) on these parameters. Methods:The study was conducted on 150 health young subjects (age 18 to 27) without any disorder which affects the lumbar spine and the discs. Subjects underwent standard standing lateral lumbar radiography. Mann-Whitney U test and Spearman's correlation test were used for statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We constructed a straight-line model of the spine composed of weighted mean values of vertebral body heights (Berry et al, 1987;Busscher et al, 2010;Kunkel et al, 2011;Nissan and Gilad, 1984;Panjabi et al, 1992Panjabi et al, , 1991Scoles et al, 1988;Singh et al, 2011;Tan et al, 2004) and intervertebral disc heights of T10-L1 (Busscher et al, 2010;Demir et al, 2018;Fang et al, 1994;Fletcher et al, 2015;Frost et al, 2019;Koeller et al, 1984;Kunkel et al, 2011;Nissan and Gilad, 1984).…”
Section: Geometrical Model Of the Spine And The Lumbosacral Spinal Cordmentioning
confidence: 99%
“…We constructed a straight-line model of the spine composed of weighted mean values of vertebral body heights (Berry et al, 1987;Busscher et al, 2010;Kunkel et al, 2011;Nissan and Gilad, 1984;Panjabi et al, 1992Panjabi et al, , 1991Scoles et al, 1988;Singh et al, 2011;Tan et al, 2004) and intervertebral disc heights of T10-L1 (Busscher et al, 2010;Demir et al, 2018;Fang et al, 1994;Fletcher et al, 2015;Frost et al, 2019;Koeller et al, 1984;Kunkel et al, 2011;Nissan and Gilad, 1984).…”
Section: Geometrical Model Of the Spine And The Lumbosacral Spinal Cordmentioning
confidence: 99%
“…Whereas several authors have reported an association of disc height with age (either disc height increases with age or decreases with age, depending on the study), the strength of the association is very important to consider. [49][50][51][52][53][54] It is also possible that reporting disc height in units of percent endplate width minimize the differences between sexes compared to studies showing a difference in disc height between males and females when disc height is measured in millimeters. 53,54 Despite that publications and spine fusion coverage policies infer interchangeability of spondylolisthesis with instability 55 , this has been proven in several studies NOT to be true.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54] It is also possible that reporting disc height in units of percent endplate width minimize the differences between sexes compared to studies showing a difference in disc height between males and females when disc height is measured in millimeters. 53,54 Despite that publications and spine fusion coverage policies infer interchangeability of spondylolisthesis with instability 55 , this has been proven in several studies NOT to be true. [56][57][58][59] There is no way to address this issue with the NHANES-II data, in large part due to the lack of validated diagnostic metrics for instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these, our study showed statistically that the anterior and posterior heights of the disc are generally preserved even in the patient group in early period after clinical signs. The progression of disc degeneration is one of the underlying pathologies of the degenerative lumbar diseases commonly seen in the elderly population (Akeda et al;Lee et al;Demir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%